Komplementäre Onkologie: ein überflüssiges Konzept? - Hübner, Jutta; Eschbach, Corinna (Der Onkologe, 2017)
Background: The number of cancer patients who are interested in complementary and alternative medicine is rising; however, currently there is no generally accepted definition of these terms. Objectives: Besides presenting a definition, the article points out the importance of complementary oncology in general and also from the point of view of the patients. Material and methods: Starting from a historical perspective including current research, current demand and patients perspectives, a definition and recommendations for patient centered counseling are presented. Results: Methods that are used in complementary medicine must be evidence-based and in accordance with the scientific state of the art. All other approaches are part of alternative medicine. More research is urgently needed within the framework of evidence-based medicine in order to allow patients to precisely and transparently differentiate between complementary and alternative medicine. The important wish of patients who want to become active and gain autonomy can be fulfilled by integrating complementary methods. The first step of complementary medicine is to give more attention to the patients, which appears to be unrealistic in modern healthcare systems. Conclusion: Some deliberation on complementary medicine seems necessary for any physician dealing with cancer patients. Knowledge on complementary and alternative medicine is one aspect but more important is communication. Confidence results from taking the patient seriously with the hopes, wishes and fears, expectations and needs. This trust is decisive at any point of care in oncology.
Online publiziert: 9. November 2016
Gesehen am 04.10.2018